الدولة في القرآن الكريم والسنة النبوية: المفهوم وحتمية الوجود - Ibrahim Mohamed, Hossam El Din; Elatrash, Radwan Jamal Yousef (Penerbit USIM, Universiti Sains Islam Malaysia (USIM), 2018)
This research focuses on elucidating the concept of state through deducing conceptions that indicate its necessary existence, and that being from the Qur’ānic perspective as well as the present reality. The research problem lies in the fact that the traditional Islamic thinkers – according to the researcher’s knowledge – did not discuss the state as a modern concept as in Western thought. This is because the state is a symbol of system and law, without which life cannot proceed properly. Also, this research highlights the difference between Islamic political thought and its Western counterpart in understanding and defining the state, as the two trends differ in culture and conviction; this was done using an inductive and analytical methodology. Highlighting the most significant results, the research proved that the state is closely connected to life, and cannot be done without for providing a good life and balanced social justice in all aspects of life, especially the political and legal.